Pemberian Pupuk N, P, dan K Berdasarkan Pengelolaan Hara Spesifik Lokasi untuk Meningkatkan Produktivitas Kedelai (Review) - KARSIDI PERMADI; YATI HARYATI (Fakultas Pertanian Universitas Udayana, 2015)
Applicationof N, P, and K Fertilizer Based on Site-Specific Nutrient Management for An increase of Productivity of Soybean. Soybean productivity in Indonesia is still low, it is about 1.25 t ha-1.This is due to the same dose of fertilizer in all location.In this case, fertilization is on the recommendation i.e. 25-75 kg urea ha-1 + 50-100 kg SP-36 ha-1 + 50-100 kg KCl ha-1 for soybean in all locations.Though each location farmland have different levels of soil fertility. Soybean commodities can compete with other plants when minimum productivity of 2.18 t ha-1 of dry beans, it is able to provide a higher profit than corn. To that end, soybean fertilizer recommended by site-specific nutrient management (SSNM) by using the method of paddy soil test device, and dry soil test device that can determine soil nutrient classes to categories of low, medium and high.N fertilizer on soil classes, including low, medium, and high dose respectively at 174, 152, and 117 kg urea ha-1. For P fertilizer application on soil nutrient classes, including low, medium, and high doserespectively at 104,80, and 40 kg ha-1 SP-36. Likewise K fertilizer application on soil nutrient classes, including low, medium, and high each at doses of 210, 190, and 150 kg ha-1 KCl. In addition, supported by the use of new varieties of soybean large seed that high productivity and achieve the results expected in all locations soybean.Then the government provides support for input subsidies in the form of primary production facilities such as seed, fertilizer, and pesticides that farmers are interested in returning to planting soybeans and soybean prices ensure incentives for farmers. Things like this will spur farmers to increase productivity so that soybean self-sufficiency is achieved. In the end domestic soybean demand can be met so that the government no longer to import soybeans.